Interactive Multimedia for Teaching Writing Descriptive Text to Junior High School Students - Syahputra, Ridwandha Eka; Wahidah, Wahidah; Afna, Mauloeddin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2022)
The article projected the outcome of a research and Development (R&D) design on an Interactive Multimedia Computer Application which was implemented to be an English Subject learning module, teaching descriptive texts, for the students at a Junior High School, SMP Swasta Dwi Tunggal, Kota Medan. The App, “Devourlish”, is a multi-platform App, capable run-on both Personal computers (PC) and Smartphones; The Google-Play and Apple-Apps Store Ecosystems. The process was formative teaching as the evaluation phases (Analysis, Design, Development, Implementation, and Evaluation) ADDIE of R&D design for the seventh grade, which was conducted in collaboration with the English teacher at the school, highlighted the students’ engagement to interactive learning apps and enlisted the students’ learning experiences on descriptive texts. The result indicated the apps was very highly practical since the average score in both phases were 3.69 and 3.74 respectively proving learning achievement as the potential effect in term of evaluated formative phases. Additionally, the apps also high potential effect after being tried out in the classroom, which is an application quality control for ADDIE in R&D design, reaching out to 80 % of the students learning achievement. Eventually, the success of the app to facilitate English subject learning experiences the effort to draw the student's interest, to make the “Devourlish” accepted, and to affect ADDIE in an R&D design.